Complex Approach to Assess Results of Surgical Correction of Eyelids Position - M. B. Gushchina; A. V. Tereshchenko; D. S. Afanasyeva (Oftalʹmologiâ)
It is not easy to assess surgery results, especially, when there are no quantitative criteria, at first sight. Results of the surgical interventions for paralytic lagophthalmos are especially difficult to assess, as the anatomic result of the surgery (position of the eyelids) influences on vision and patient’s appearance with an impact on their life quality. Purpose: to develop a complex approach to assess results of surgery for paralytic lagophthalmos. The proposed complex approach includes objective and subjective components. The objective component describes main functions of vision and dynamics of eyelids position with coefficient of symmetry and coefficient of surgical efficacy. The subjective component covers dynamics of ocular discomfort, patient significant eyelids and palpebral fissure deformity, and quantity of artificial tears dropping. The proposed approach can be used to assess results of surgery, including for comparison of the different surgeries, for paralytic lagophthalmos as well as for other ocular pathology with eyelids malposition and palpebral fissure deformity.